Growing Solid Rock - Biorock as a Nature-Inspired Combination of Eco-Friendly Materials and Resilient Marine Ecosystems - Faag,Julia (2026)
Acidification-threatened marine ecosystems and competition for land use along the coasts are merely some of the consequences of the climate crisis. A technology with growing interest that can contribute to solutions for these consequences is Biorock. As a nature-inspired approach based on electrolysis of seawater, Biorock offers two solutions in one technology; eco-friendly materials grown directly in the seawater and resilient marine ecosystems. So far, Biorock has mainly been used in tropical waters, making its function in colder waters an under-researched area. Therefore, the objective of this thesis is to explore the potential of the Biorock-technology to contribute to favorable habitats for marine ecosystems and to eco-friendly materials in a Swedish context. To achieve this objective, a literature study and personal communications with authors and experts were carried out. The results show that the growing material can store carbon and protect against corrosion but at a relatively slow and non-linear growth rate. It also appeared to have physical properties similar to concrete. Moreover, the material structure and growth process depend on several factors. Regarding marine ecosystems, Biorock can contribute to some of the Swedish climate and biodiversity goals by providing a refuge with favoring water chemistry and natural materials, increasing their resilience against climate change. One identified challenge is, however, choosing an electrical stimulation level suitable for both marine ecosystems and useful materials. Overall, it is evident that the strengths of Biorock lie not in large-scale acidification mitigation or energy- and cost-effective material production or carbon storage. Instead, its values are multifunctionality and sustainability. There are reasons for considering the growing material a solid rock, not just because of its physical strength but also because its benefits make Biorock a “solid rock”, a potential solution, in the unstable climate crisis. Therefore, apart from the seawater structures, with more research attention, Biorock might as well be growing on us.
Keywords: Biorock; Seacrete; Seament; electrodeposition; electrolysis of seawater; marine ecosystems; eco-friendly materials; artificial reef; corrosion; breakwater; acidification; carbon dioxide emissions; carbon storage; pollution capture; environment; climate